IMPLEMENTATION OF THE TEAM GAME TOURNAMENT MODEL WITH EDUCATIONAL LUDO MEDIA TO INCREASE INTEREST IN LEARNING HISTORY OF STUDENTS OF CLASS X MAN 1 KUANTAN SINGINGI: PENGGUNAAN MODEL TEAM GAME TOURNAMENT DENGAN MEDIA LUDO EDUKATIF UNTUK MENINGKATKAN MINAT BELAJAR SEJARAH SISWA KELAS X MAN 1 KUANTAN SINGINGI - Inez Pramulia Dewi; Isjoni; Yanuar Al Fiqri (SOSIOEDUKASI, 2026)
History learning still faces various problems, one of which is the low interest in learning of students. This is characterized by a lack of student enthusiasm, one-way class discussions, lack of questions, and low attention to learning materials. The low interest in learning is influenced by the lack of innovation in the learning process. This research aims to increase students' interest in learning history through the application of the Team Game Tournament (TGT) learning model with Ludo Educative media. This research is a Class Action Research (CAR) which was carried out on students of class X.2 MAN 1 Kuantan Singingi in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The data collection technique uses observation and questionnaires, while the data analysis is carried out in a quantitative descriptive manner. The results showed that student learning activities in the first cycle reached 64.05% and increased in the second cycle to 85.97%, exceeding the success indicator of 60%. Students' interest in learning in the first cycle obtained an average percentage of 76.45% and increased in the second cycle to 84.40%, and has met the success indicator of 80%. Thus, the application of the Team Game Tournament learning model with Educational Ludo media has proven to be effective in increasing students' interest in learning history subjects in class X.2 MAN 1 Kuantan Singingi.